Pengaruh Kualitas Pelayanan Terhadap Minat Pemanfaatan Ulang Pelayanan Rawat Jalan Puskesmas Tumbu-Tumbu Jaya Konawe Selatan - Resti Nur Pratiwi; Nani Yuniar; Jafriati Jafriati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Good health services are services that can be obtained by the community effectively, safely, and of high quality to those in need supported by adequate resources. Judging from the initial research data, the research location has many obstacles related to health services. The purpose of this study was to analyze the effect of service quality on the interest in reusing outpatient services at the Tumbu-tumbu Jaya Health Center, Konawe Selatan. This type of research is a survey with a cross sectional study design. The population of this research is the people of East Kolono District who have received health services as many as 331 people. The research sample was 181 people. The results showed that the 5 variables studied, 4 variables that have a significant relationship to the interest in reusing health services, namely tangibles, p-value = 0.000, reliability, p-value = 0.001, responsiveness, p-value = 0.046 and assurance obtained. result p-value = 0.000. While empathy has no relationship to the interest in reusing health services, the p-value = 0.468 is obtained. Simultaneous multivariate test using binary logistic regression test shows that tangible has a significant relationship to the interest in re-utilizing outpatient services with p-value = 0.000 meaning that tangible is the determining factor of all variables. The conclusion of the study is that the interest in reusing outpatient services is most closely related to tangibles.